The Effect of Service Quality on Customer Loyalty with Brand Images and Customer Satisfaction as Mediation - Adhitya Narotama (Jurnal Manajemen dan Kewirausahaan, 2019)
This study aims to determine the effect of service quality on customer loyalty with brand images and customer satisfaction as mediation. This research is a quantitative correlational type using non probability sampling. The number of sample are 400 customers of BRI Branch Office on Soekarno Hatta Malang. Data is processed using Partial Least Square (PLS) method. The results show: 1) The service quality has a significant effect on customer satisfaction; 2) The service quality has a significant effect on brand images; 3) The service quality has no effect on customer loyalty; 4) The customer satisfaction has a significant effect on customer loyalty; 5) The brand images has no effect on customer loyalty; 6) The effect of service quality on customer loyalty through customer satisfaction is a significant.; 7) The effect of service quality on customer loyalty through brand images is an insignificant.https://doi.org/10.26905/jmdk.v7i1.2692